Dehydrogenation of Propane over Silica‐Supported Platinum–Tin Catalysts Prepared by Direct Reduction: Effects of Tin/Platinum Ratio and Reduction Temperature. Issue 9 (14th August 2014) - Deng, Lidan; Miura, Hiroki; Shishido, Tetsuya; Hosokawa, Saburo; Teramura, Kentaro; Tanaka, Tsunehiro
Abstract A series of Pt‐Sn/SiO2 catalysts with different Sn/Pt atomic ratios (1/3–3) were prepared by a direct reduction method and tested for the dehydrogenation of propane to propylene. Structural characterization by XRD, TEM, CO adsorption, X‐ray photoelectron spectroscopy, and X‐ray absorption fine structure analysis revealed that the Pt‐Sn/SiO2 catalysts possessed a highly dispersed Pt‐Sn alloy core with a Sn‐rich surface regardless of the Sn/Pt ratio or reduction temperature. Highly dispersed SnO2 coexisted with the Pt‐Sn alloy particles, and part of the Pt‐Sn alloy surface was covered with SnO2. Among the catalysts prepared, 1Pt1Sn/SiO2_1073 K (Sn/Pt ratio=1, reduced at 1073 K), composed of Pt3Sn alloy with a small fraction of Pt‐Sn alloy, exhibited the highest activity. In contrast, if the Sn/Pt ratio was larger than 1 and/or the reduction temperature was 1273 K, Pt‐Sn alloy was observed mainly and the Pt‐Sn/SiO2 catalysts showed low activity.